Effect of water hardness on fertilisation and hatching success of Clarias gariepinus (Burchell, 1822) and Heterobranchus longifilis valenciennes, 1840 eggs fertilised with C. gariepinus sperm - Ofor, Chukwuma Okereke (2019)
The effect of water hardness on fertilisation and hatching of eggs of Heterobranchus longifilis Valenciennes, 1840 and Clarias gariepinus (Burchell, 1822) was studied. Eggs were obtained from five artificially-induced females of each species. Milt from five male C. gariepinus was suspended in 5 mL physiological saline and mixed with 100 g eggs from a homogenised egg mass from five individuals of each species. Two mL aliquots containing 294±4 and 274±8 C. gariepinus and H. longifilis eggs respectively were incubated at 27 oC in groups of quadruplicate troughs containing water of 20, 80, 160, 300 mg.L⁻¹ CaCO3, and control dilution medium of 8 mg.L⁻¹ CaCO3 total hardness. Fertilisation and hatching rates were compared between species using a t-test. Effect of hardness on the variables was determined using the ANOVA. Water hardness level did not significantly affect fertilisation rate of C. gariepinus eggs (p>0.05), while H. longifilis eggs were significantly affected.